Pressurized intraperitoneal aerosolized chemotherapy clinical efficacy in the combined treatment of newly diagnosed ovarian cancer with peritoneal carcinomatosis and ascites - A. S. Dzasochov; A. A. Kostin; V. L. Astashov; M. A. Andreeva; A. B. Turiev; N. Yu. Urazovskii (Исследования и практика в медицине)
Purpose of the study. To study the clinical efficacy of pressurized intraperitoneal aerosolized chemotherapy (PIPAC), which complements the combined treatment of ovarian cancer with peritoneal carcinomatosis.Patients and methods. The study included 175 patients with newly diagnosed ovarian cancer with peritoneal carcinomatosis (87 in the main group, 88 in the control group). All patients underwent extirpation of the uterus with appendages, removal of the large omentum and chemotherapy according to the TC scheme (Taxol, Carboplatin). In the main group, 3 additional sessions of PIPAC were performed. The duration of relapse‑free survival, PCI index, ascites volume and peritoneal morphology were evaluated.Results. Complete regression of carcinomatosis was noted in the second session of PIPAC, in 44 (52.4 %) patients (PCI = 0); complete resorption of ascites – in 74 (88.1 %); complete therapeutic pathomorphosis – in 48 (57.2 %) cases. Complete regression of carcinomatosis was noted in the third session of PIPAC in 73 cases (87.0 %), complete resorption of ascites in 80 cases (95.2 %), complete morphological pathomorphosis in 69 cases (82.2 %). 6 months after treatment, complete regression of carcinomatosis (PCI = 0) was detected in 81 patients (96.4 %), complete resorption of ascites in 83 (98.8 %), complete morphological regression in 72 (85.7 %). The advantage of the main group in terms of median relapse‑free survival was 7 months.Conclusion. Ascites resorption, a decrease in the PCI index and drug pathomorphosis of peritoneal metastases, detected during the 2nd session of PIPAC, had an increasing dynamics during treatment and persisted for a long time. From our point of view, the advantage in median relapse‑free survival in the main group is due to the local effect of PIPAC, which complemented the standard treatment of ovarian cancer with peritoneal carcinomatosis.